PENGARUH KESADARAN WAJIB PAJAK, PENGETAHUAN KORUPSI TERHADAP KEPATUHAN WAJIB PAJAK DI KPP PRATAMA MEDAN TIMUR (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2021)
The motivation behind this studywas to decide whether citizen awareness and their insight into debasement corresponded as far as citizen consistency at KPP Pratama Medan Timur. We overviewed 139,327 citizens. In this review, 125 citizens were tested utilizing the accommodation inspecting strategy. Examination of information I fixed it utilizing illustrative insights and relapse investigation with enlightening examination and numerous srelapsese. Based on what happened to examiner and the following analysis: (1). Taxpayer awareness influences and contributes to 9,36% of taxpayer compliance at KPP Pratama Medan Timur. (2). Knowledge of corruption influences and contributes 4,16% of tax compliance at KPP Pratama Medan Timur. KPP Pratama Medan is advised to conduct in-depth and intensive socialization or counseling to increase understanding and awareness of taxpayer compliance or citizens to pay taxes on time.